2017
DOI: 10.5009/gnl16099
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Levofloxacin-Based Third-Line Therapy for the Eradication of Helicobacter pylori in Peptic Ulcer Disease

Abstract: Background/AimsThe resistance rate of Helicobacter pylori is gradually increasing. We aimed to evaluate the efficacy of levofloxacin-based third-line H. pylori eradication in peptic ulcer disease.MethodsBetween 2002 and 2014, 110 patients in 14 medical centers received levofloxacin-based third-line H. pylori eradication therapy for peptic ulcer disease. Of these, 88 were included in the study; 21 were excluded because of lack of follow-up and one was excluded for poor compliance. Their eradication rates, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Levofloxacin triple regimen or rifabutin triple regimen is suggested as rescue therapy by the guidelines [ 6 , 18 ]. However, Lim et al reported in 2017 that the eradication rate of levofloxacin triple regimen as third-line treatment was 56.9% in Korea [ 37 ]. This low eradication rate can be explained by the high-resistance rate to levofloxacin in Korea [ 28 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Levofloxacin triple regimen or rifabutin triple regimen is suggested as rescue therapy by the guidelines [ 6 , 18 ]. However, Lim et al reported in 2017 that the eradication rate of levofloxacin triple regimen as third-line treatment was 56.9% in Korea [ 37 ]. This low eradication rate can be explained by the high-resistance rate to levofloxacin in Korea [ 28 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This regimen is also recommended as a secondary therapeutic option after failure of 1st-line eradication therapy [6,15]. The efficacy of levofloxacin-based triple therapy as first line treatment was reported as 52.5-65.3%, while the efficacy as third line treatment was 71.6% in Korea [16][17][18]. According to this result, levofloxacin-based regimen seems to be a possible option for rescue therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of ofloxacin to standard triple therapy has been shown to augment eradication rates, while gemifloxacin was inferior to clarithromycin‐based therapies . A review of levofloxacin‐based third‐line therapy over the past decade in Korea found pooled eradication rates of 71.6% throughout the decade, suggesting no increase in resistance rates over the past decade . A 10‐day triple therapy containing ilaprazole, levofloxacin, and amoxicillin reported good results, with an eradication rate of 88.8% …”
Section: Fluoroquinolonesmentioning
confidence: 99%